Effect of Ethanolic Extract of Ketip Banana Peel (Musa paradisiaca forma typiaca) Improves Sperm Viability of Mice (Mus musculus) Following Cigarette Smoke Exposure - Saputra, Jagat; Bahri, Syamsul; Setiadi, Dadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Cigarette smoke exposure is known to induce oxidative stress that adversely effect male reproductive function, including sperm viability. This study aimed to evaluate the effect ethanolic extract of Ketip banana peel (Musa paradisiaca forma typiaca) on sperm viability on mice (Mus musculus) exposed to cigarette smoke. The experiment employed a factorial design with two factors: duration of cigarette smoke exposure (0, 5, 15, and 30 minutes) and concentration of banana peel ethanol extract (0, 250, and 750 ppm). Sperm viability was assessed using standard microscophic evaluation methods. Stastictical analysis revealed that administration of the ethanolic extract significantly increased sperm viability in cigarette smoke exposed mice, as indicated by an F-value (Fcalculatede = 3604.294) exceeding the critical Ftabel value (3.9777790). the results suggest that the ethanolic extract of Ketip banana peel exerts a protective effect against cigarette smoke-induced reproductive toxicity, potentially due to its antioxidant properties. Therefore, Ketip banana peel extract has promising potential as a natural agen for impeoving sperem quality under oxidative stress conditions.